Letter from Thomas Coke to Patricia Whiting, October 19, 1965 - Whiting, Patricia, 1940-2010:::Creator::::::::::::
A letter from the Foreign Student Advisor at San Jose State College thanking Whiting for her participation in a campus fashion show.